1997
DOI: 10.1212/wnl.48.4.891
|View full text |Cite
|
Sign up to set email alerts
|

Stroke recurrence

Abstract: We compared stroke severity, risk factors, and prognosis in patients with recurrent versus first-ever stroke. In the Copenhagen Stroke Study, we prospectively studied 1,138 unselected patients with acute stroke. Stroke was recurrent in 265 (23%) despite most of these patients being given prophylactic treatment prior to recurrence. Only 12% of patients with atrial fibrillation were receiving anticoagulant treatment prior to recurrence. In multivariate analysis, recurrence was more frequently associated with a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
172
1
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(186 citation statements)
references
References 0 publications
8
172
1
2
Order By: Relevance
“…We found that the rate of recurrent stroke was remarkably higher in the patients with poor functional outcome. Because prognosis of recurrent stroke was unfavorable, 29 it is possible that subsequent stroke instead of minor stroke or TIA per se led to functional disability in our study.…”
Section: Strokementioning
confidence: 87%
“…We found that the rate of recurrent stroke was remarkably higher in the patients with poor functional outcome. Because prognosis of recurrent stroke was unfavorable, 29 it is possible that subsequent stroke instead of minor stroke or TIA per se led to functional disability in our study.…”
Section: Strokementioning
confidence: 87%
“…Vol.7 No.2:87 2016 with higher mortality than first stroke and functional recovery is often poorer [9,23]. The available data on stroke patients suggest that medication persistence is often sub-optimal, and that many patients are consequently at a significantly increased risk of a further stroke [6,13,16].…”
Section: Journal Of Neurology and Neuroscience Issn 2171-6625mentioning
confidence: 99%
“…The increased risk of recurrent stroke due to diabetes ranges from 2.1 to 5.6 times that of nondiabetic patients (154,156) and is independent of glucose control during the interstroke period (163). The significance of these findings is underscored by the increased morbidity and mortality associated with recurrent stroke (164).…”
Section: Hypercoaguability Conferred By Diabetes -mentioning
confidence: 99%